Study the Effects of Formaldehyde and Xylene Vapor on Lung and Testicular Tissue with Sperm Morphology of Adult Albino Rats - Trefa F. Ismail; Galawezh O. Othman; Naznaz H. Othman; Ban A. Hassan (Polytechnic Journal)
Formalin is widely used chemical substance in industry and medicine (as tissue fixative and disinfectant). It contains reactive molecules which have been known for its cytotoxic effects. Furthermore, xylene used in histological techniques during preparation of tissue and has different toxic effects on tissues. The present study was performed to investigate the effects of formaldehyde and xylene inhalation on albino rat’s lung and testes. Fifteen adult male rats were used in this study; the rats were divided randomly into three groups (A, B, and C). Group (A) comprises the control group, whereas the rats in the Group (B) were exposed to 10% formaldehyde vapor and the rats from Group (C) were exposed to xylene vapor for 4 h/day for 5 days/week for 1 month. Histological alterations were observed in the lung of formalin and xylene exposed rats manifested by lymphatic infiltration, emphysema, congestion, dilation of blood vessels, and alveolar sac and also thinning in the wall of alveolar bronchiole. On the other hand, formaldehyde and xylene affected the testes tissue of treated rats including atrophy in the seminiferous tubule cells, edematous connective tissue, degenerative of spermatogenesis, depletion in germinal layer, existing of vacuoles in the seminiferous tubules, and decrease in the number of sperms in the lumen of seminiferous tubules. Furthermore, sperms abnormalities were seen. The data of our study concluded that inhalation the vapor of formaldehyde and xylene has degenerative effects on lungs and testes of the experimental rats as well as affecting on the spermatocytes and increased the frequency of sperm abnormalities.